The discourse of nursing students about the palliative care with the hospitalized elderly - Marins, Aline Miranda da Fonseca; França, Kissyla Harley Della Pascôa; Duarte, Sabrina da Costa Machado; Cardoso, Maria Manuela Vila Nova (Revista Kairós-Gerontologia, 2020)
This study proposal sought to identify the perception of the student from the last year of the nursing graduate course about the finiteness of the elderly in the context of palliative care. The participants were twenty students who revealed the difficulties in relation to the care with the hospitalized elderly, the fear of death and of being unable to deal with this situation. There is a need for previous preparation of the student to develop the care with the elderly, with an emphasis on skills and abilities to be enhanced in the work routine.